Assessing the impact of blocking distal coronary sinus-left atrial muscular connection on inducible rate of atrial fibrillation and follow-up recurrence in persistent atrial fibrillation patients with different fibrotic degrees of left atrial: A retrospective study - Zhang, FeiLong; Liu, JiChun; Fang, Ping; Wang, XiangHai; Wang, JinFeng; Wei, YouQuan; Yang, Hao (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: The musculature of the coronary sinus (CS), especially its distal connection with the post wall of the left atrial (LA), has been associated with the genesis and maintenance of atrial flutter (AFL) and atrial fibrillation (AF). However, the relative contributions of the distal coronary sinus (CSD)-LA connection to PersAF with various degrees of atrial fibrosis remain unknown. Objective: This study aimed to explore the different roles of blocking the CSD-LA connection in the induction of acute AF and middle-term follow-up of recurrence among PersAF patients with various degrees of LA fibrosis. Methods and Results: A retrospective cohort of 71 patients with drug-refractory and symptomatic PersAF underwent ablation for the first time were studied. The population was divided into two groups according to disconnection of the CSD-LA or not. All patients enrolled accepted the unified ablation procedure (circumferential pulmonary vein isolation, non-pulmonary vein trigger ablation and ablation of the CSD-LA connection). Group A (n = 47) successfully blocked the CSD-LA electrical connection and Group B (n = 24) failed. Twenty-five patients could be induced into sustained AF in the Group A compared to 20 in the Group B (53.2% vs 83.3%, p=0.013). After a mean follow-up of 185±8 days, 24 (33.8%) patients experienced atrial arrhythmia recurrences. The Group A had significantly fewer recurrences (25.5%) compared to Group B (50%). Meanwhile, in Group A, the ROC curve analysis suggested that in the case of blocking CSD-LA, low voltage area (LVA) of LA can act as a predictive factor for acute AF induction (AUC=0.943, Cut-off=0.190, P＜0.001) with sensitivity and specificity of 92.3% and 90.5%, and middle-term recurrence (AUC=0.889, Cut-off=0.196, P＜0.001) with sensitivity and specificity of 100% and 65.7%. Conclusions: Disconnection of CSD-LA could reduce the inducible rate of acute AF and the recurrences of atrial arrhythmia during middle-term follow-up. The PersAF patients with CSD-LA muscular connection blocked, experienced a higher acute AF inducible rate with larger proportion of LVA of LA (≥ 19%) and a higher recurrent rate of atrial arrhythmias with a larger proportion of LA fibrosis (≥ 19.6%).